Holographic design of leaky‐wave antenna with gain controlled four beams. Issue 3 (12th December 2018) - Liu, Jinlin; Su, Tao; Wu, Bian; Lv, Huanhuan
Abstract: In this article, a holographic design of leaky‐wave antenna (LWA) with gain controlled 4 beams using artificial impedance surface (AIS) is presented. The AIS is composed of sub‐wavelength patches which have small physical sizes and less loss. Based on the principle of the holographic theory, the radiation pattern with 4 beams can be obtained with the AIS excited by the reference wave. By adjusting the amplitude coefficients of the modulation depth of each beam, the gain of each beam can be effectively controlled. For validating the analysis, a prototype is fabricated and measured. The results show that the proposed method is an efficient way to design gain controlled 4‐beam LWA.